A Single-Center Experience of Correlation of Pulse Pressure to Mortality of Stroke Hemorrhage Patients in Indonesia - Feda Anisah Makkiyah; Saraah Dicha; Rahmah Hida Nurrizzka (The Scientific World Journal)
Introduction. The relationship between pulse pressure and mortality in acute stroke hemorrhage patients is a subject of debate. To investigate this relationship in the Indonesian context, a study was conducted due to the increasing prevalence of stroke in the country. Methods. The study sample consisted of 111 patients with acute stroke hemorrhage admitted to the hospital between January 1, 2016, and December 31, 2019. Patients with sepsis, cancer, or other hematology disorders were excluded, as were those who were lost to follow-up. Statistical analysis was performed using SPSS 22, and correlations were evaluated between various patient characteristics and laboratory values. Results. It was revealed that patients with a wider pulse pressure were more likely to die (adjusted odds ratio = 3,070) than those with a normal or constricted pulse pressure. Conclusion. Pulse pressure had an impact on the mortality of patients with acute hemorrhagic stroke.